2021
DOI: 10.1021/acs.jpcc.1c05259
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Rectification of Carboxylate-Terminated Self-Assembled Monolayer Junction by Humidity and Alkali Metal Ions: The Coupling and Asymmetric Factor Matter

Abstract: Facile modulation of the rectification behavior of a molecular junction device was achieved by humidity and alkali metal ions using a series of carboxylic acid-terminated self-assembled monolayers (COOH SAMs) on gold and eutectic gallium-indium alloy top contact (EGaIn). The rectification ratio (RR) increased significantly as the humidity (ranging from 1 to 39%) increases for an n-mercaptoalkanoic acid (HSC n O2H, n = 11, 12, 14, 16) SAM device. Meanwhile, K+/Na+, as the counterion of COO– in the same element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 100 publications
(151 reference statements)
0
10
0
Order By: Relevance
“…Using the conventional thermal evaporation method, a 60 nm gold film was prepared on a clean Si(100) wafer with a SiO 2 layer. ,, The clean Si(100) wafer was placed inside a vapor deposition chamber. Chromium (5 nm) as an adhesive layer was evaporated followed by 60 nm Au at a vacuum of 1 × 10 –6 mbar with evaporation rates of 0.05 and 1.0 Å/s, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Using the conventional thermal evaporation method, a 60 nm gold film was prepared on a clean Si(100) wafer with a SiO 2 layer. ,, The clean Si(100) wafer was placed inside a vapor deposition chamber. Chromium (5 nm) as an adhesive layer was evaporated followed by 60 nm Au at a vacuum of 1 × 10 –6 mbar with evaporation rates of 0.05 and 1.0 Å/s, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is unexpected since the electronic structure of the SAM layer in both cases is indistinguishable as listed in Table . We noticed that Ai et al among others reported the resistance of the SAM layer based on the carboxylic-terminated thiol molecule using EGaIn top contact was influenced by the humidity. However, in our junction, we exclude the effect of H 2 O used during the formation of the SAM layer since the low-bias resistance of Au/SC 11 COOH/Au is 2 orders of magnitude smaller than that of Au/SC 11 CH 3/ Au junction.…”
mentioning
confidence: 90%
“…It is unexpected since the electronic structure of the SAM layer in both cases is indistinguishable as listed in Table 1. We noticed that Ai et al 21 among others 26 reported the resistance of the SAM layer based on the carboxylic-terminated thiol molecule using EGaIn top contact was influenced by the humidity. However, in our Next, we made AFM tips coated with other metals including Ag and Pt and then studied the effect of work functions on the low-bias resistance.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Here, a method for breaking adhesive interfaces is proposed and relies on the ability of one of the materials at the adhesive interface to be functionalized with a small molecule self-assembled debonding layer that contains a cleavable covalent bond. Self-assembled thin layers, e.g., self-assembled monolayers (SAMs), have been used at a variety of interfaces for a number of different applications, such as surface reaction modifiers, chemical probes, electronics insulators, and adhesion promoters. The method developed here depends on a chemical change in the system rather than a mechanical change to achieve debonding. Specifically, this research explores the ability of a silane-based debonding layer on silica to debond polymer adhesives from the silica surface.…”
Section: Introductionmentioning
confidence: 99%